IJABE has successfully been covered and indexed in Thomson Reuter’s Web of Science Core Collection - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
DOI: 10.3965/j.ijabe.20140704.001 Citation: Wang Y K. IJABE has successfully been covered and indexed in Thomson Reuter’s Web of Science Core Collection. Int J Agric & Biol Eng, 2014; 7(4): 01－02. I received a formal letter in late July which was signed by Marian Hollingsworth, the Publisher Relations Director of Thomson Reuters, which confirmed that the International Journal of Agricultural and Biological Engineering (IJABE) has been selected for complete coverage in Thomson Reuter’s products and services. Beginning with V. 6(1) 2013, IJABE will be indexed and abstracted in: ♦ Science Citation Index Expanded (also known as SciSearch®) ♦ Journal Citation Reports/Science Edition ♦ Current Contents®/Agriculture, Biology, and Environmental Sciences ♦ Biological Abstracts ♦ BIOSIS Previews